Effective suppression of nonlinear distortion in optical phase conjugation of optical OFDM signals using backward Raman pumping. Issue 4 (1st October 2016) - Huang, Chaoran; Shu, Chester
ABSTRACT: The use of backward Raman amplification to mitigate nonlinear distortion in optical phase conjugation (OPC) of orthogonal frequency-division multiplexing (OFDM) signals in a fibre communication system is investigated in this paper. A ∼29 dB reduction in the nonlinear distortion is achieved, while comparable conjugated output signal power is maintained through the Raman gain. By numerically solving the nonlinear Schrödinger equation (NLSE) along the fibre, a detailed theoretical model is developed to elaborate the mechanism in Raman-assisted OPC. Different optical network scenarios have been analysed using this model. The mechanism of Raman-assisted OPC is further explained by comparing the power profiles of both the conjugated signal and the nonlinear distortion with those in the conventional scheme. In addition to investigating the nonlinear distortion caused by spurious four-wave mixing (FWM) products, the waveform distortion resulting from pump depletion in the OPC system is also analysed. The linearity in Raman-assisted and conventional OPC systems is characterised and compared. The result shows a power deviation reduction of ∼14 dB through Raman amplification.